(untitled) (Research, Society and Development, 2020)
The current article aims to investigate if micro and small businesses, classified as micro companies/ small businesses, are obliged to present balance sheet registered in corresponding body in biddings according to law 123/2006. To that end, we use a clipping in the law nº 10.406/02 text, Brazilian Civil Code, or by Complementary Law nº 123/06, applicable to the micro company and to the small business, yet aggregated to Managemt Board of Simples Nacional resolutions and also of the Accounting Federal Board as General Technical Interpretation resolution 1000, through bibliographic and descriptive methodology. It was verified that the obligatoriness of the anual accounting bookkeeping by the Micro Companies and Small businesses is crucial to take part in bidding events, besides being essential to data provision to controlling and decising making.